Exploring the Relationship Between Teacher and Multilingual Student Discourse During Small Group Text-Based Discussions - Budde, Christina M.; Marcus, Margaret Sullivan; Martin-Beltran, Melinda; Silverman, Rebecca D. (Language and Literacy / Langue et littératie)

(untitled) (Language and Literacy Researchers of Canada, 2022)
Few studies investigate how teacher discourse moves relate to subsequent student discourse moves in real-time small-group reading instruction with multilingual learners (MLLs). Grounded in sociocultural theory and classroom discourse research, this study examines how fourth-grade MLLs engage in reasoning discourse during text-based discussions. We argue that by examining reasoning discourse holistically - beyond speaker turns - we can capture teacher-talk moves that facilitate or constrain student reasoning. This examination illuminates discourse practices such as “procedural instruction” and “reference to text,” with important consequences for MLLs. Our study has implications for scholarship analyzing classroom talk and literacy educators facilitating discussions where MLLs engage in sophisticated and complex reasoning discourse.